Hydrogels with tunable mechanical plasticity regulate endothelial cell outgrowth in vasculogenesis and angiogenesis - Wei, Zhao; Lei, Meng; Wang, Yaohui; Xie, Yizhou; Xie, Xueyong; Lan, Dongwei; Jia, Yuanbo; Liu, Jingyi; Ma, Yufei; Cheng, Bo; Gerecht, Sharon; Xu, Feng (Nature communications, 2023)
The endothelial cell (EC) outgrowth in both vasculogenesis and angiogenesis starts with remodeling surrounding matrix and proceeds with the crosstalk between cells for the multicellular vasculature formation. The mechanical plasticity of matrix, defined as the ability to permanently deform by external traction, is pivotal in modulating cell behaviors. Nevertheless, the implications of matrix plasticity on cell-to-cell interactions during EC outgrowth, along with the molecular pathways involved, remain elusive. Here we develop a collagen-hyaluronic acid based hydrogel platform with tunable plasticity by using compositing strategy of dynamic and covalent networks. We show that although the increasing plasticity of the hydrogel facilitates the matrix remodeling by ECs, the largest tubular lumens and the longest invading distance unexpectedly appear in hydrogels with medium plasticity instead of the highest ones. We unravel that the high plasticity of the hydrogels promotes stable integrin cluster of ECs and recruitment of focal adhesion kinase with an overenhanced contractility which downregulates the vascular endothelial cadherin expression and destabilizes the adherens junctions between individual ECs. Our results, further validated with mathematical simulations and in vivo angiogenic tests, demonstrate that a balance of matrix plasticity facilitates both cell-matrix binding and cell-to-cell adherens, for promoting vascular assembly and invasion. It is vital to unveil the effects of extracellular matrix cues on endothelial cell (EC) outgrowth for desirably governing vasculature formation, but the role of matrix plasticity on EC outgrowth is elusive. Here, the authors develop hydrogels with tunable mechanical plasticity independent of stiffness, and elucidate the plasticity-mediated responses of ECs during vasculogenesis and angiogenesis.